Pharmaceutical assistance in autoimmune diseases: lupus and vitiligo, a literature review (Research, Society and Development, 2022)
Autoimmune diseases arise when a malfunction of the immune system occurs, which causes the cells of the body to attack the tissues of the body itself. Unfortunately, autoimmune diseases though not contagious have no cure. Systemic lupus erythematosus and vitiligo are two chronic autoimmune diseases that can significantly impact patients’ quality of life. Systemic lupus erythematosus affects several regions of the body, most frequently the skin, where it causes a red and scaly rash. Vitiligo also affects areas of the skin, causing patches of discoloration in various shapes and sizes. The objective of this study was to explain the importance of pharmaceutical assistance in coping with effects of lupus and vitiligo, by decreasing disease activity and controlling long term symptoms. Information was gathered through bibliographic review, in the databases: Scientific journals, SCIELO, Google Scholar, ANVISA website and BVS regional portal, referring to the theme. Taking into account the results, we found research with patients with the diseases, who had pharmaceutical follow-up and those who did not. We concluded that in view of the positive effect of pharmaceutical assistance on the treatment of autoimmune diseases, the pharmaceutical professional has an important role in monitoring these diseases and achieving the desired therapeutic objectives for these patients, including a better quality of life.